Enhancing visitation in the child welfare system for children separated from their birth parents: pilot results of fostering relationships - Burtch, Elisabeth Neely; Macera, Elisa; Shauffer, Carole; Gupta, Aanya; Dozier, Mary (Attachment & human development, 2025)
When children are placed into foster care, they experience separations from their primary attachment figures. Visitations are often arranged to provide ongoing birth parent-child contact. These visitations are complicated, though, because young children typically show a range of confusing behaviors when reunited. Fostering Relationships is a brief intervention designed to enhance visitation for the child, birth parent, and foster parent. We examined the effectiveness of the Fostering Relationships intervention through single subject analyses. We examined whether birth parents followed their child's lead during visitation sessions significantly more than they did not follow their child's lead. Six of seven birth parents who received the Fostering Relationships intervention followed their child's lead significantly more often than not, whereas only one of four of the control parents did so. Results are preliminary, but suggest that Fostering Relationships may be a promising intervention for enhancing visitation.